2017
DOI: 10.1186/s13287-017-0616-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of equine endometrial mesenchymal stromal cells

Abstract: BackgroundEquine mesenchymal stromal/stem cells (MSCs) are most commonly harvested from bone marrow (BM) or adipose tissue, requiring the use of surgical procedures. By contrast, the uterus can be accessed nonsurgically, and may provide a more readily available cell source. While human endometrium is known to harbor mesenchymal precursor cells, MSCs have not been identified in equine endometrium. This study reports the isolation, culture, and characterization of MSCs from equine endometrium.MethodsThe presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 48 publications
(44 reference statements)
0
33
0
Order By: Relevance
“…Intrauterine infusions of mares with autologous conditioned serum [101], allogenic bone marrow-derived mesenchymal stem cells (MSCs) [101], or autologous endometrial MSCs [102] revealed the anti-inflammatory properties of these treatments. This suggest their possible prophylactic or therapeutic use in mares susceptible to persistent endometritis [101,102]. Due to the lack of available therapies, currently equine endometrosis is regarded as an irreversible disease [3,8].…”
Section: Molecular Research To Improve Treatmentmentioning
confidence: 99%
“…Intrauterine infusions of mares with autologous conditioned serum [101], allogenic bone marrow-derived mesenchymal stem cells (MSCs) [101], or autologous endometrial MSCs [102] revealed the anti-inflammatory properties of these treatments. This suggest their possible prophylactic or therapeutic use in mares susceptible to persistent endometritis [101,102]. Due to the lack of available therapies, currently equine endometrosis is regarded as an irreversible disease [3,8].…”
Section: Molecular Research To Improve Treatmentmentioning
confidence: 99%
“…A recently published study revealed, for the first time, a successful attempt to obtain MSCs from the horse's uterus [27]. Researchers demonstrated the presence, in the endometrium, of cells that fit the definition of mesenchymal stem cells.…”
Section: Equine Stem Cellsmentioning
confidence: 99%
“…MSCs were originally isolated from the bone marrow [11], but later they have been obtained from nearly all tissues of the body, including adipose tissue [12,13], umbilical cord blood [14], umbilical cord Wharton's jelly [15,16], allanto-amniotic membranes [17], synovia [18], periost [13], skeletal muscle [13], teeth [19], placenta [20] or endometrium [21]. All of them were sources of MSCs, as determined by morphology, adherence to plastic, trilineage differentiation, and detection of stem cell surface markers with immunofluorescent and flow cytometric analyses.…”
Section: Sources Of Mscsmentioning
confidence: 99%